Meneladani Spiritualitas Kerendahan Hati Yesus Lewat Salib dan Kalvari: (Perspektif Armada Riyanto Dasar Filsafat Remah dan Daun Kering) - Nikodemus, Nikodemus; Andreas Jimmy (Jurnal Pendidikan Agama dan Teologi, 2024)
This research study has a theological aim of the meaning of Spirituality of Humility in a Christian context experiencing a crisis of faith. The background to the writing is the author's observation of several phenomena in the practical life of Christians in modern times which are experiencing degradation, such as lack of willingness, sacrifice, humility, love and faith. The problems experienced by the author believe are due to problems with Christian spirituality in modern times. The author observes the fact that modern humans do not appreciate the events of the cross and calvary (Jesus). This experience provides the principles of spirituality, crumbs and dry leaves, which can answer the problems of modern times. The spirituality of humility brings humans to become friends of Jesus. The author uses descriptive and bibliographic analysis methods. The author conducted a theological study of the meaning of spiritual humility from Eko Armada Riyanto's book "The Spirituality of Crumbs and Dry Leaves". The book used will show problems, which can be answered through the principles of spirituality based on humility. The results of this study are the basis for the implementation of Christian spirituality today. The author hopes to help, increase insight into the spiritual life of Christian life. Spirituality of humility brings people closer to God in whom they believe, spirituality makes people moved by love and affection in their lives. Spirituality brings humans to a deep awareness, especially humility, that comes from God. Becoming humble requires a very long process, so openness to God's love makes humans friends to all and willing to be shaped by God.